Search for heavy resonances decaying to two Higgs bosons in final states containing four b quarks - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Erö, J.; Flechl, M.; Friedl, M.; et al. (My University, 2016)
A search is presented for narrow heavy resonances X decaying into pairs of Higgs bosons (H) in proton-proton collisions collected by the CMS experiment at the LHC at s=8TeV. The data correspond to an integrated luminosity of 19.7fb-1. The search considers H H resonances with masses between 1 and 3TeV, having final states of two b quark pairs. Each Higgs boson is produced with large momentum, and the hadronization products of the pair of b quarks can usually be reconstructed as single large jets. The background from multijet and t t ¯ events is significantly reduced by applying requirements related to the flavor of the jet, its mass, and its substructure. The signal would be identified as a peak on top of the dijet invariant mass spectrum of the remaining background events. No evidence is observed for such a signal. Upper limits obtained at 95 % confidence level for the product of the production cross section and branching fraction ?(gg?X)B(X?HH?bb¯bb¯) range from 10 to 1.5 fb for the mass of X from 1.15 to 2.0TeV, significantly extending previous searches. For a warped extra dimension theory with a mass scale ?R= 1 TeV, the data exclude radion scalar masses between 1.15 and 1.55TeV. © 2016, CERN for the benefit of the CMS collaboration.
Citation: Khachatryan, V., Sirunyan, A. M., Tumasyan, A., Adam, W., Asilar, E., Bergauer, T., . . . Collaboration, C. M. S. (2016). Search for heavy resonances decaying to two Higgs bosons in final states containing four b quarks. European Physical Journal C, 76(7). doi:10.1140/epjc/s10052-016-4206-6